SLC25A46 is required for mitochondrial lipid homeostasis and cristae maintenance and is responsible for Leigh syndrome. Issue 9 (7th July 2016) - Janer, Alexandre; Prudent, Julien; Paupe, Vincent; Fahiminiya, Somayyeh; Majewski, Jacek; Sgarioto, Nicolas; Des Rosiers, Christine; Forest, Anik; Lin, Zhen‐Yuan; Gingras, Anne‐Claude; Mitchell, Grant; McBride, Heidi M; et al.
Abstract: Mitochondria form a dynamic network that responds to physiological signals and metabolic stresses by altering the balance between fusion and fission. Mitochondrial fusion is orchestrated by conserved GTPases MFN1/2 and OPA1, a process coordinated in yeast by Ugo1, a mitochondrial metabolite carrier family protein. We uncovered a homozygous missense mutation in SLC25A46, the mammalian orthologue of Ugo1, in a subject with Leigh syndrome. SLC25A46 is an integral outer membrane protein that interacts with MFN2, OPA1, and the mitochondrial contact site and cristae organizing system (MICOS) complex. The subject mutation destabilizes the protein, leading to mitochondrial hyperfusion, alterations in endoplasmic reticulum (ER) morphology, impaired cellular respiration, and premature cellular senescence. The MICOS complex is disrupted in subject fibroblasts, resulting in strikingly abnormal mitochondrial architecture, with markedly shortened cristae. SLC25A46 also interacts with the ER membrane protein complex EMC, and phospholipid composition is altered in subject mitochondria. These results show that SLC25A46 plays a role in a mitochondrial/ER pathway that facilitates lipid transfer, and link altered mitochondrial dynamics to early‐onset neurodegenerative disease and cell fate decisions. Synopsis: Whole‐exome sequencing in a Leigh syndrome patient identified mutations in SLC25A46, a degenerate member of the mitochondrial metabolite transport family, linking altered mitochondrial dynamics to early‐onset neurodegenerative disease. Loss of SLC25A46 results in mitochondrial hyperfusion and striking changes in mitochondrial architecture. SLC25A46 is an outer membrane protein that interacts with MFN2, OPA1, the MICOS complex, and the EMC complex in the ER. Loss of SLC25A46 results in altered ER morphology and marked changes in the phospholipid composition of the mitochondrial membranes. Loss of SLC25A46 results in premature cellular senescence in dividing cells. Abstract : Whole‐exome sequencing in a Leigh syndrome patient identified mutations in SLC25A46, a degenerate member of the mitochondrial metabolite transport family, linking altered mitochondrial dynamics to early‐onset neurodegenerative disease.